Efektivitas Program Bantuan Pangan Non Tunai (BPNT) di Desa Tolotio Kecamatan Tibawa Kabupaten Gorontalo - Olis Bawode; Arifin Tahir; Yacob Noho Nani (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
The Non-Cash Food Assistance Program (BPNT) is a government policy aimed at reducing the expenditure burden of poor households through the provision of food assistance in non-cash form. However, its implementation at the village level still faces various challenges. This study aims to analyze the effectiveness of the BPNT Program in Tolotio Village, Tibawa District, Gorontalo Regency, and to identify the factors influencing its implementation. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, field observations, and document analysis involving village government officials, the Social Affairs Office, BPNT facilitators, and beneficiary communities. The results indicate that the implementation of BPNT in Tolotio Village is relatively effective in supporting food needs and enhancing the independence of Beneficiary Families (KPM). Nevertheless, several issues remain, including inaccurate targeting of beneficiaries, limited technological literacy, and insufficient transparency and updating of beneficiary data. The factors affecting program effectiveness include the availability of implementing resources, the support of physical facilities and technology, the effectiveness of communication among stakeholders, and the level of community acceptance and response. The findings imply the need for regular data updating, improved socialization, and strengthened coordination and supervision to ensure that the BPNT Program is implemented more fairly, accurately targeted, and sustainably.